Influence of Age on Global and Regional Brain Stiffness in Young and Middle‐Aged Adults - Takamura, Tomohiro; Motosugi, Utaroh; Sasaki, Yu; Kakegawa, Takashi; Sato, Kazuyuki; Glaser, Kevin J.; Ehman, Richard L.; Onishi, Hiroshi (Journal of magnetic resonance imaging, 2020)
Background An understanding of potential age‐related changes in brain stiffness and its regional variation is important for further clinical application of MR elastography. Purpose To investigate the effect of age on global and regional brain stiffness in young and middle‐aged adults. Study Type Prospective. Subjects Fifty subjects with normal brains and aged in their 20s, 30s, 40s, 50s, or 60s (five men, five women per decade). Field Strength/Sequence 3.0T MRI and elastography with a vibration frequency of 60 Hz. Assessment Stiffness was measured in nine brain regions (cerebrum, temporal lobes, sensorimotor areas, frontotemporal composite region, deep gray matter and white matter (deep GM/WM), parietal lobes, occipital lobes, frontal lobes, and cerebellum) using an atlas‐based region‐of‐interest approach. The influence of age on regional brain stiffness was evaluated. Statistical Tests Multiple linear regression analysis, followed by Dunnett's multiple comparisons test, using subjects in their 20s as controls. Results Following adjustment for sex, multiple linear regression revealed a significant negative correlation between age and stiffness of the cerebrum (P < 0.0001), temporal lobes (P < 0.0001), sensorimotor areas (P < 0.0001), frontotemporal composite region (P < 0.0001), deep GM/WM (P = 0.0028), parietal lobes (P < 0.0001), occipital lobes (P = 0.0055), and frontal lobes (P < 0.0001). Dunnett's multiple comparison test showed that the stiffness of the sensorimotor areas, frontotemporal composite region, and frontal lobes was significantly decreased in subjects in their 40s (P < 0.0367), 50s (P < 0.0001), and 60s (P < 0.0001), while that of the cerebrum, temporal lobes, and parietal lobes was significantly decreased only in subjects in their 50s (P < 0.0012) and 60s (P < 0.0031) when compared with the controls. Data Conclusion There is an age‐related decrease in brain stiffness that varies across the different regions. Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;51:727–733.